1996
DOI: 10.1177/002224299606000303
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Helping Behavior: An Integrative Framework for Promotion Planning

Abstract: Charitable organizations play a vital role in our society, as is evidenced by their enormous economic and social impact. Yet, for many of them, soliciting adequate resources to carry out their mandates is a continuing struggle. Confronted with a growing need for their services, fierce competition from other charities, and shrinking support from government agencies, charities may turn to marketers for help in developing effective promotional strategies. Unfortunately, marketing literature is unable to provide m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
298
0
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(312 citation statements)
references
References 72 publications
6
298
0
8
Order By: Relevance
“…Intra-organizational volunteerism as charitable support behavior Similar to OCB, charitable support behavior has been found to be motivated by both altruistic and egoistic factors (Bendapudi et al, 1996;Piliavin and Charng, 1990). The altruistic motivation behind much CSB is often referred to as ''warm glow'' feelings (Andreoni, 1990) which captures the emotion connected with pro-social helping behavior, a feeling that in itself is motivating, similar to the ''high'' that motivates many recreational runners.…”
Section: Intra-organizational Volunteerismmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-organizational volunteerism as charitable support behavior Similar to OCB, charitable support behavior has been found to be motivated by both altruistic and egoistic factors (Bendapudi et al, 1996;Piliavin and Charng, 1990). The altruistic motivation behind much CSB is often referred to as ''warm glow'' feelings (Andreoni, 1990) which captures the emotion connected with pro-social helping behavior, a feeling that in itself is motivating, similar to the ''high'' that motivates many recreational runners.…”
Section: Intra-organizational Volunteerismmentioning
confidence: 99%
“…Further, the norms enforced in work groups or within the larger corporate context can be an effective means of encouraging CSB, since individual CSB has been shown to be highly responsive to social pressure (Fisher and Ackerman, 1998;LaTour and Manrai, 1989) and the need for affiliation (Broadbridge and Horne, 1994). For example, pro-social behavior has been shown to increase when the help is solicited from within the individual's social network (Bendapudi et al, 1996). In the workplace context, Amos (1982) revealed that certain forms of CSB might even be an explicit condition of employment.…”
Section: Intra-organizational Volunteerismmentioning
confidence: 99%
“…As in traditional marketing, one of the utilitarian goals of this type of research is to understand the most adequate means to stimulate people's generosity. Research on charity marketing is also widespread (Bendapudi et al 1996;Michel and Rieunier 2012). Beyond determining the qualities of donors (i.e., identifying the characteristics of those who donate to notfor-profit organizations), marketing research also tries to understand what drives ''altruistic'' behaviors, like giving money, time, blood, or even organs (Fennis et al 2009).…”
Section: The Four Main Areas Of Marketing Research Where the Concept mentioning
confidence: 99%
“…The Need to Give Gratuitously: A Relevant Concept Anchored in Catholic Social Teaching… Concerning charitable giving, Sargeant and Jay (2004) and Bendapudi et al (1996) propose different explanations than altruism for individual engagement. Some donors give time and energy because of the connections they want to cultivate with or within the charity, like making friends or introducing themselves through the charity.…”
Section: The Four Main Areas Of Marketing Research Where the Concept mentioning
confidence: 99%
See 1 more Smart Citation